Juridical Review Adjustment of Legal Entity Political Parties and New Political Parties to become Legal Entities Based on Law Number 2 of 2011 concerning Political Parties - Ananto, Riana Wulandari (Law Research Review Quarterly, 2018)
The existence of political parties is a means of governing political communication and government, namely the community. The function of political communication is intended as one party that formulates interests (interests articulation) and challenges or distributes interest (aggregation interest) of the community to be conveyed and fought for by the government through available channels, while in other positions it also explains and disseminates government policies to the public (specifically member of the political party concerned). Law Number 2 of 2011 concerning Amendments to Law Number 2 of 2008 concerning Political Parties, requires legal entities or new political parties to register as legal entities in accordance with Law Number 2 of 2011 concerning Political Parties, This is a circle to further institutionalize the structure of national political party management. Therefore, the provisions of article 3 paragraph (2) stipulate that political parties become police bodies that have a police force of atleast 75% of the total provinces, 50% of the total number of districts/ cities in each province that discuss, and 50% of the total number of sub-districts in each province, district/ city in the area concerned.